Aplikasi schedule pengerjaan proyek online dinas PU Kab. Sidrap - Wahyuddin, Wahyuddin; Saputra, Asmar (Fakultas Teknik Universitas Muhammadiyah Parepare, 2021)
Research Schedule Retrieval of Online Project Work Application for Public Works Agency of Kab. Sidenreng Rappang. Aims to create programs that can optimize the process of monitoring the progress of project work. The research method used is Field Research (Field Studies) and Literature Review. Created a system Process data project work schedule that will provide convenience when inputting data and processing to produce reports on project work data. From the test results using the Black Box, by studying the list of programs obtained by the system which is done after inputting the project data scheduling testing in accordance with the application. With a Web Hosting System so that the resulting project management schedule management system is expected to help in managing the project work schedule online.